A climate‐driven tree line position model in the White Mountains of California over the past six millennia. (7th March 2018) - Bruening, Jamis M.; Bunn, Andrew G.; Salzer, Matthew W.
Abstract: Aim: Position of the alpine tree line ecotone around the globe corresponds to a growing season isotherm of approximately 6°C. Accordingly, tree lines are important indicators of Holocene global and regional environmental change. A central line of inquiry in tree line ecology is to better understand the mechanisms that dictate tree line position on the landscape, as well as the environmental conditions that cause upslope and downslope shifts in its position at centennial to millennial time‐scales. Here, we present a climate‐driven model to predict tree line position over the past 6, 000 years. Location: Sheep Mountain, located in the White Mountain Range of California, USA. Time period: 4750bce to present. Major taxa studied: Great Basin bristlecone pine ( Pinus longaeva BK Bailey). Methods: We use a climate‐driven tree line position model that utilizes a topoclimate raster surface of growing season average temperature to predict the spatial position and area of the alpine tree line ecotone across the mountain range. We then produce a time series of tree line position predictions at 500‐year intervals from 4750bce to present, and compare the predictions to the growth dates and spatial locations of 61 remnant bristlecone pine samples from above modern tree line. Results: The model indicates that tree line position in the White Mountains, CA migrated downslope throughout the Holocene until approximately 750ce, rebounded slightly upslope by 1250ce, and has since likely remained stationary. Applying the model under present‐day climatic conditions suggests the current tree line at Sheep Mountain may be out of climatic equilibrium by up to 250 vertical metres in some places. Conclusion: The results support independent conclusions from global tree line analyses, underscore the temperature sensitivity of the tree line ecotone, and further develop our understanding of climate‐driven tree line dynamics.